Molecular recognition by Ig-like receptors, KIRs and Fc gamma Rs - Maenaka, K; Van Der Merwe, P; Stuart, D; Sondermann, P; Jones, E (2001)
Structural studies by us and other groups have shown that Killer cell Ig-like receptors (KIRs) and Fc gamma receptors (Fc gammaR) have a similar, unique topology (intermediate between I set and C2 set). In order to gain further insight into molecular recognition by these receptors, we have used surface plasmon resonance (SPR) to analyze the kinetic and thermodynamic properties of their interactions with their natural ligands.A repertoire of KIRs with two or three tandem Ig domains in their extracellular regions is expressed on human natural killer (NK) cells. These KIRs activate or inhibit NK cell cytotoxicity following recognition of MHC class I molecules on target cells. Different two-domain KIRs (KIR2Ds) recognise distinct subsets of HLA-C alleles. SPR analysis showed that, like other cell-cell recognition molecules interactions, the KIR2DL3 binds peptide-HLA-Cw7 with a low affinity (Kd similar to 10(-5)M), fast kinetics, and favourable entropic changes. In contrast, recent studies have shown that TCR/peptide-MHC interactions are characterised by slow kinetics and highly unfavourable entropic changes. Thus, although the TCR and KIRs both show allele- and peptide-specific MHC recognition, they bind with very different thermodynamic and kinetic properties.Fc gamma receptors (Fc gammaR) are expressed on immunologically active cells, bind the Fc portion of IgG and contribute to phagocytosis, cytotoxicity and the clearance of immune complexes. SPR analysis showed that the human low-affinity Fc gamma Rs (Fc gamma RIIa, Fc gamma RIIb and Fc gamma RIII) bind Fc with fast kinetics and a low affinity (Kd similar to 10(-6)M), as observed with other cell-cell recognition interactions, including KIR/HLA interactions. Interestingly, whereas the Fc gamma RIIa/Fc and Fc gamma RIIb/Fc interactions exhibited favourable entropic changes, comparable to the KIR/HLA interaction, the Fc gamma RIII/Fc interaction was characterized by large unfavourable entropic changes.